Hygiene in small-scale poultry slaughterhouses in Thailand: An Ecohealth/One Health approach case study - Chotinun, S.; Suwan, M.; Unger, Fred; Tohtubtiang, K.; Rojanasthien, S. (Khon Kaen University, 2013)
Background and justification Thailand is the one of the world’s poultry meat production countries. However, small scale rural poultry production development can be challenged by food safety policies that can limit economic development opportunities for this sector. This may led to reduced incentives for improving sanitation and disease prevention along the poultry production chain. Furthermore, many cases of Salmonellosis in human are reported year by year. Previous reports revealed that slaughterhouses play a role of disease spreading sources. According to the Department of Livestock Development (DLD), most of the poultry slaughterhouses in Thailand are small scale and improper management was commonly observed.